IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING EXTENSIVE READING AT SMP MUHAMMADIYAH LUWUK - Abdul Rabbi Arrasul; Nursina Abdul Halim (BABASAL English Education Journal, 2021)
The objective this research is to look for the improvement of students’ vocabulary mastery through extensive reading at  SMP  Muhammadiyah  Luwuk. This research used a pre-experimental research design with one group pretest and posttest design. The population of this research was  the students of ninth grade students  of  SMP Muhammadiyah Luwuk  consisted of twenty-two students. The sample of this research  was all the population of the research. In collecting data, the researcher used test. The test consisted of pretest and posttest. Data were analyzed statistically. After being analyzed, it was found that the result of the t-counted was 12,215. With 21 degree of freedom, and a the significance level of 0,05, the t-table was 1,721.Therefore, the result of t-counted is bigger than t-table. It is clear that the research hypothesis is received. In other words, the implementation of extensive reading can improve students’ vocabulary mastery of the ninth grade students at SMP Muhammadiyah Luwuk.